Optical control of ERK and AKT signaling promotes axon regeneration and functional recovery of PNS and CNS in Drosophila - Qin Wang; Huaxun Fan; Feng Li; Savanna S Skeeters; Vishnu V Krishnamurthy; Yuanquan Song; Kai Zhang (eLife, 2020)
Neuroregeneration is a dynamic process synergizing the functional outcomes of multiple signaling circuits. Channelrhodopsin-based optogenetics shows the feasibility of stimulating neural repair but does not pin down specific signaling cascades. Here, we utilized optogenetic systems, optoRaf and optoAKT, to delineate the contribution of the ERK and AKT signaling pathways to neuroregeneration in live Drosophila larvae. We showed that optoRaf or optoAKT activation not only enhanced axon regeneration in both regeneration-competent and -incompetent sensory neurons in the peripheral nervous system but also allowed temporal tuning and proper guidance of axon regrowth. Furthermore, optoRaf and optoAKT differ in their signaling kinetics during regeneration, showing a gated versus graded response, respectively. Importantly in the central nervous system, their activation promotes axon regrowth and functional recovery of the thermonociceptive behavior. We conclude that non-neuronal optogenetics targets damaged neurons and signaling subcircuits, providing a novel strategy in the intervention of neural damage with improved precision.